Biopreservation of Hepatocytes: Current Concepts on Hypothermic Preservation, Cryopreservation, And Vitrification - Fuller, Barry J. (2016)
Isolated liver cells (primarily isolated hepatocytes) have found important applications in science and medicine over the past 40 years in a wide range of areas, including physiological studies, investigations on liver metabolism, organ preservation and drug de-toxification, experimental and clinical transplantation. An integral component of many of these works is the need to store the isolated cells, either for short or long-term periods. This review covers the biopreservation of liver cells, with a focus on the history of liver cell biopreservation, the application of hypothermia for short-term storage, standard cryopreservation methods for isolated hepatocytes, the biopreservation of other types of liver cells, and recent developments such as vitrification of hepatocytes. By understanding the basis for the different approaches, it will be possible to select the best options for liver cell biopreservation in different applications, and identify ways to improve preservation protocols for the future.